A Report on the Emergence of FinTech Companies in India - Divya Kapoor (Journal of Advanced Research in Accounting and Finance Management, 2024)
Economic conflicts such as knowledge inequality and economic power are similar economies of scale and breadth, resulting in financial intermediaries. These conflicts possess the energy to shape the structure of the market. The advancements in technology are not new finance, it has taken extraordinary steps in associating connecting systems, computer power and cost, and newly built and usable data. These developments have proved to be very beneficial in terms of costs, efforts, and use. The economy of scale, scope, and network results have led to customer acquisition, funding, compliance activities, data, and capital. Regardless of innovative advances, clientele search and the expense of mix stays significant. These situations encourage reunification and give benefits to major suppliers of many products, including big players in the market. Potential consequences in terms of competition, focus, and market structure include "barbell". The result is made up of a few major providers and many niche players. Authorities should cooperate on all financial guidelines, competition, and industry regulatory bodies in order to promote stability and integrity, competitiveness and efficiency, and consumer protection and privacy.